Surface‐Enhanced Raman Spectroscopy for the Detection of a Metabolic Product in the Headspace Above Live Bacterial Cultures. (7th November 2018) - Kelly, Jessica; Patrick, Robin; Patrick, Sheila; Bell, Steven E. J.
Abstract: In situ surface‐enhanced Raman spectra of the headspace above cultures of six bacterial species showed strong characteristic bands from chemisorbed methyl sulfide. This marker compound is created by dissociation of dimethyl disulfide (DMDS), a fermentative metabolite of bacteria, on the surface of the enhancing Au or Ag nanoparticle films. Kinetic binding plots of media spiked with DMDS and of live cultures showed that the Au‐based substrates were more suitable for the rapid detection of bacteria than Ag‐based substrates. For E. coli DH5α, the sensitivity limit for headspace SERS detection was 1.5×10 7  CFU mL −1, which corresponded to detection 15 min after inoculation of the growth medium. Since the metabolites are only produced by viable bacteria, antibiotic (gentamicin) treatment stopped the normal signal growth of the marker peak. This work is a promising step towards rapid bedside detection of bacterial infections and rapid screening of antibiotics against bacteria.